A benchmark dose analysis for urinary cadmium and type 2 diabetes mellitus. (15th March 2021) - Shi, Peng; Yan, Huanchang; Fan, Xingjun; Xi, Shuhua
Abstract: Cadmium (Cd) is a heavy metal referred to as one of the environmental endocrine disruptors. The dose-dependent association between Cd and type 2 diabetes mellitus (T2DM) has been elucidated, but the corresponding threshold has not been established. To evaluate the urinary Cd levels associated with T2DM, we perform a benchmark dose (BMD) analysis based on data from the 1999–2006 National Health and Nutrition Examination Survey (NHANES). Weighted datasets were generated by the inverse probability of treatment weighting analysis to develop the robustness of our analysis. We inferred a strong positive association between urinary Cd and T2DM in unweighted and weighted populations. BMD and its low limit (BMDL) estimates for 5% benchmark responses (BMR) was 0.297 (0.198) and 0.190 (0.178) μg/g creatinine for each population, respectively. The sensitivity analysis by race, followed by weight of sum method showed similar estimates of urinary Cd level for the risk of developing T2DM, which are rather low and far less than those for the renal or bone disease development risk. This indicates that T2DM can be a sensitive outcome of Cd exposure and therefore should be taken into account in the development of standard regulatory limits for safe exposure to Cd. Graphical abstract: Image 1 Highlights: We computed the urinary cadmium benchmark doses for type 2 diabetes mellitus. For benchmark response of 5%, the benchmark dose was 0.190 μg/g creatinine. For benchmark response of 10%, the benchmark dose was 0.230 μg/g creatinine. Benchmark doses of urinary cadmium were generally low for type 2 diabetes mellitus. Abstract : As the T2DM prevalence increased, estimating BMDs and BMDLs of exposure to Cd can help decision-making in developing these standard limits.